Alcohol Binge Drinking Selectively Stimulates Protein S-Glutathionylation in Aorta and Liver of ApoE−/− Mice - Seidel, Kerstin; Wan, Xueping; Zhang, Mo; Zhou, Yuxiang; Zang, Mengwei; Han, Jingyan (Frontiers in Cardiovascular Medicine, 2021)
Background Binge drinking has become the most common and deadly pattern of excessive alcohol use in the United States, especially among younger adults. It is closely related to the increased risk of cardiovascular disease. Oxidative stress as a result of ethanol metabolism is the primary pathogenic factor for alcohol-induced end organ injury, but the role of protein S-glutathionylation—a reversible oxidative modification of protein cysteine thiol groups that mediates cellular actions by oxidants—in binge drinking-associated cardiovascular disease has not been explored. The present study sought to define the effect of binge drinking on the formation of protein S-glutathionylation in cardiovascular system of mouse model of atherosclerosis. Methods and Results To mimic the weekend binge drinking pattern in humans, ApoE deficient (ApoE−/−) mice on the Lieber-DeCarli liquid diet received ethanol or isocaloric maltose (as a control) gavages (5 g/kg/day, 2 consecutive days/week) for a total of 6 weeks. The primary alcohol-target organs (liver, brain), and cardiovascular system (heart, aorta, lung) of these two groups of mice were assayed for the protein S-glutathionylation levels and its regulatory enzyme system [Glutaredoxin1(Grx1), glutathione reductase (GR), glutathione -S-transferase Pi (GST- π)], as well as aortic endothelial function and liver lipid accumulation. We found that binge drinking selectively stimulated protein S-glutathionylation in aorta, liver, and brain, which coincided with altered glutathionylation regulatory enzyme system that is downregulated Grx1 and upregulated GST-π in aorta, massive upregulation of GST- π in liver, and no changes in Grx1 and GST-π in brain. Functionally, binge drinking induced fatty liver and damaged aortic endothelial cell function were reflected by increased permeability and reduced flow-mediated vasodilation. Conclusions This study is the first to provide in vivo evidence for differential effect of binge drinking on formation of protein S-glutathionylation and its enzymatic regulation system in major alcohol-target organs and cardiovascular system. The selective induction of protein S-glutathionylation in aorta and liver is associated with aortic endothelial dysfunction and fatty liver, which may be a potential redox mechanism for the increased risk of cardiovascular disease in binge-drinkers.